A phylogenetic approach to determining the importance of constraint on phenotypic evolution in the neotropical lizard Anolis cristatellus (2017)
Question: Is the pattern of phenotypic divergence among populations influenced by constraint in the form of the genetic covariances among characters? Background: Quantitative genetic theory predicts that when evolutionary lineages diverge simultaneously by genetic drift, the pattern of among-population divergence will parallel the pattern of within-population genetic variation and covariation. Among-population divergence is measured by the variance–covariance matrix of population means (the D matrix), or by the variance–covariance matrix of independent contrasts (DIC). The latter avoids the assumption of simultaneous divergence by incorporating phylogenetic non-independence among lineages and was developed expressly for this study. Within-population genetic variation and covariation are measured by the additive genetic variance–covariance matrix (the G matrix). Organism: The Puerto Rican crested anole (Anolis cristatellus). Methods: We sampled A. cristatellus from seven divergent populations widely dispersed across the species’ range. These populations are sufficiently highly diverged to be considered evolutionarily independent lineages. We substituted the phenotypic variance–covariance matrix (P matrix) for G in evolutionary analysis. (Empirical studies have shown that P and G are frequently highly correlated for morphological traits.) In two populations, we estimated phenotypic variance–covariance matrices (P matrices) for 13 skeletal morphological traits, while in the remaining five we estimated mean phenotypes for the same traits. To test the hypothesis of constraint, we first calculated a pooled phenotypic variance–covariance matrix (P¯¯) from all populations. We compared P¯¯ to the variance–covariance matrix of population means (D) and of independent contrasts (DIC). Independent contrasts were calculated using a molecular phylogeny of the included lineages. Results: Comparison of P matrices between populations showed evidence that covariance structure is highly conserved in conspecific populations of A. cristatellus. Comparison of P¯¯ with D and of P¯¯ with DIC indicated significant similarity in both cases, suggesting that constraint has influenced phenotypic evolution and thus probably genotypic evolution in this species.